Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Two Stay-Two Stray di Sekolah Dasar - Syukria Padilah Hasibuan; Nur Azmi Alwi (Universitas Negeri Padang, 2023)
This study aims to describe the increase in student learning outcomes in integrated thematic learning using models Two Stay Two Stray in grade-V SDN 17 Manggis Ganting, Bukittinggi City. This type of research is classroom action research (CAR) which is carried out in two cycles, cycle I consist of 2 meetings, and Cycle II consists of 1 meeting. Each cycle includes four stages: planning, implementing, observing, and reflecting. The subjects of this research were teachers and 24 students. Collection data techniques in the form of observation, tests, and non-tests. The approach used a qualitative approach and a quantitative approach. The results of the RPP research cycle I averaged 80.5% with qualification (B) and cycle II averaged 94.44% with qualification (A). Implementations of the learning process aspects of the teacher cycle I averaged 82.81% with qualifications (B) and cycle II averaged 96.87% with qualifications (A), the implementation of student aspects of the cycle I averaged 82.81% with qualifications (B) and cycle II average 96.87% with qualification (A). Assessment of students learning outcomes in cycle I obtained an average of 79.25 (C) and cycle II an average of 91.5 (A). Based on these results it can be concluded that the model Two Stay Two Stray can improve the integrated thematic learning outcomes of students in elementary schools.